Effectiveness of Health Education on the Knowledge and Attitudes of Pregnant Women in the Prevention of Preeclampsia: Scoping Review - Shineka Nur Alviolita; Andari Wuri Astuti; Islamiyatur Rokhmah (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2026)
Background: Preeclampsia remains one of the leading causes of high maternal morbidity and mortality rates globally. This scoping review aims to identify and map scientific evidence on the effect of health education on pregnant women's knowledge and attitudes regarding preeclampsia, particularly in increasing knowledge, changing positive attitudes, and efforts during pregnancy. Method: This study used a scoping review design with reference to the Arksey and O'Malley framework as a guideline for conducting a scoping review. Literature searches were conducted through the PubMed, ScienceDirect, Wiley, and Google Scholar databases. The articles included were publications from 2016 to 2025 that discussed health education and the knowledge and attitudes of pregnant women regarding the prevention of preeclampsia. The article selection process followed the PRISMA-ScR guidelines. Data were extracted and mapped based on the research objectives, study design, respondent characteristics, type of health education, and main findings. Result: Ten articles were included. A total of 80% of studies reported low baseline knowledge and attitudes toward preeclampsia among pregnant women. All studies (80%) showed an increase in knowledge following health education interventions (counseling, group education, leaflets,audiovisual media). Approximatelely 70% of studies reported improvements in attitudes, and 60% showed positive changes in preventive behaviors. Conclusion: Health education is an effective and consistent intervention in improving pregnant women’s knowledge and attitudes towards preeclampsia prevention. Its implementation must be standardized and integrated into antenatal care through structured and innovative media-based approaches, with an emphasis on not only knowledge improvement but also sustained behavioral change.